Modification of land‐atmosphere interactions by CO2 effects: Implications for summer dryness and heat wave amplitude. Issue 19 (9th October 2016) - Lemordant, Léo; Gentine, Pierre; Stéfanon, Marc; Drobinski, Philippe; Fatichi, Simone
Abstract: Plant stomata couple the energy, water, and carbon cycles. We use the framework of Regional Climate Modeling to simulate the 2003 European heat wave and assess how higher levels of surface CO2 may affect such an extreme event through land‐atmosphere interactions. Increased CO2 modifies the seasonality of the water cycle through stomatal regulation and increased leaf area. As a result, the water saved during the growing season through higher water use efficiency mitigates summer dryness and the heat wave impact. Land‐atmosphere interactions and CO2 fertilization together synergistically contribute to increased summer transpiration. This, in turn, alters the surface energy budget and decreases sensible heat flux, mitigating air temperature rise. Accurate representation of the response to higher CO2 levels and of the coupling between the carbon and water cycles is therefore critical to forecasting seasonal climate, water cycle dynamics, and to enhance the accuracy of extreme event prediction under future climate. Key Points: Stomatal closure reduction under higher CO2 concentration conserves soil water during springtime and increases temperature Springtime saved water enables increased transpiration and consequent temperature mitigation during the summer Inclusion of CO2 physiological effect is essential for future heat wave and seasonal prediction as it alters land‐atmosphere feedbacks